Advances in Ceramics - Characterization, Raw Materials, Processing, Properties, Degradation and Healing 2011
DOI: 10.5772/19122
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Isotope Exchange in Nanocrystal Oxides

Abstract: Investigations on bulk samplesMost often, OIE studies on bulk samples involve isothermal annealing of samples in oxygen (or other oxygen-containing gas) enriched with 18 О isotope and measurement of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 15 publications
2
11
0
1
Order By: Relevance
“…Let us note two important points related to the use of expressions such as (1). At first, it was established [6] that the values of the particle radius r in (1) were close to the average size of coherent scattering regions experimentally determined by X-ray diffraction analysis. It means that molecules or atoms of 18 О oxygen almost freely penetrate into the space between nano-sized particles.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Let us note two important points related to the use of expressions such as (1). At first, it was established [6] that the values of the particle radius r in (1) were close to the average size of coherent scattering regions experimentally determined by X-ray diffraction analysis. It means that molecules or atoms of 18 О oxygen almost freely penetrate into the space between nano-sized particles.…”
Section: Resultsmentioning
confidence: 83%
“…1 corresponds to the case when the bulk oxygen diffusion in the oxide particles is negligible. In this case, the time variation of the average concentration of 18 O isotope C(t) in the samples is due to isotopic exchange between gaseous oxygen 18 O 2 and the outer atomic layer of the oxide particles; the corresponding theoretical expression upon condition of free access of oxygen molecules to the particles surface has a form [6]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that mechano-activation of oxides MnO, Mn 2 O 3 Mn 3 O 4 and MnO 2 substantially activates processes of their interaction with the gas phase. The models for the description of experimental data on the kinetics of isotopic exchange were suggested, the frequency of the isotopic exchange of oxides with the gas phase on the surface were set, and new data on the volume diffusion coefficients D V of oxygen in the manganese oxides were obtained [20][21][22][23]. The obtained values of the pre-exponential factor in D V for oxides Mn 2 O 3, Mn 3 O 4 [21] indicate a very low concentration of structural vacancies in them.…”
Section: Diffusion In Advanced Materialsmentioning
confidence: 99%
“…В последнее время было выполнено несколько работ, в которых для исследования водородной и кислородной подсистем оксидов была применена ускорительная методика ядерного микроанализа (NRA). С ее помощью были получены данные о кислородном и водородном изотопном обмене и коэффициентах диффузии атомов кислорода и дейтерия в оксидах [1][2][3]. Кроме того, для проведения исследований по поверхностной стехиометрии оксидов и диффузии в них дейтерия были разработаны две оригинальные методики, основанные на применении NRA.…”
Section: Introductionunclassified